BRICS Nations and Income Convergence: An Insight from the Quarterly Data for 2006Q1–2017Q2. Issue 4 (August 2021) - Das, Ramesh Chandra; Das, Utpal; Das, Amaresh
The formation of the BRICS Group was aimed at, among others, developing parallel economic power house of the highly emerging nations and generating additional shock absorbing capacity. Maintaining equitable distribution of income and wealth among the group members, thus, was one of the top most priorities of the group. Under this backdrop, the present study examines whether the countries are converging in income leading to overall development in the group. Applying the neoclassical growth and panel unit roots models on the quarterly data from 2006Q1–2017Q2 to 2009Q1–2017Q2, the study reveals that there is no significant catching up of the countries in both the periods, but there is conditional convergence in the first period. The variables which played conditional roles are net FDI inflow and crude oil production. Further, the study observes sigma convergence among the group members in both the periods, signifying that the cross-country income differences have been going down over time.